Preparation method of energy storage wire and cable adhesive
By using silicone rubber, carbon black, stearic acid and flame retardant in wire and cable glue, and adding calcite additives and silicon carbide regulators, the problem of difficult coordination between dielectric and flame retardant performance of existing wire and cable glues is solved, which is significantly Improves the product's weather resistance and UV stability.
Patent Information
- Application Number
- CN202411626287.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The dielectric properties and flame retardant properties of existing wire and cable glue are difficult to balance, and the weather resistance and UV resistance are poor, which limits the efficiency of the product.
Silicone rubber is used as the main raw material, combined with carbon black, stearic acid and flame retardant, and energy storage wire and cable glue is prepared through kneading and vulcanization molding processes by adding calcite additives and silicon carbide regulators.
The flame retardant and dielectric properties of wire and cable glue are achieved, and the weather resistance and UV stability of the product is improved, and the efficiency of the product is significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable adhesives, and in particular to a method for preparing energy storage wire and cable adhesive. Background Art
[0002] Wires and cables are cables used to transmit electricity, signals and data. They are composed of one or more insulated wires and are covered with a protective layer. Wires and cables have a simple structure and are soft, easy to bend and easy to install. They are widely used in various fields such as electricity, communications, construction, railways, aviation, and home appliances. The adhesive materials used for energy storage are also becoming more and more popular. In the preparation and application of existing wire and cable adhesives, the preparation process is simple, and the obtained cable adhesive products have poor dielectric properties and poor flame retardant properties. It is difficult to coordinate and balance the flame retardant and dielectric properties of the products. In addition, the weather resistance and UV resistance of the products are poor, which limits the use efficiency of the products. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing energy storage wire and cable adhesive to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing an energy storage wire and cable adhesive, comprising the following steps: Step 1: Weigh the raw materials by weight: 10-15 parts of silicone rubber, 4-6 parts of calcite additive, 3-5 parts of silicon carbide regulator, 4-7 parts of flame retardant, 2-5 parts of carbon black, 2-4 parts of stearic acid, 1-3 parts of dimethyl silicone oil, 2-4 parts of dicumyl peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
[0005] Preferably, the silicone rubber is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 110-115° C., and the mixing time is 20-30 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
[0006] Preferably, the preparation method of the calcite additive is: S01: 5-8 parts of calcite, 2-4 parts of sodium silicate solution, and 1-3 parts of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 4-6 parts of dry flaky talc, 1-3 parts of nano-silica sol, and 2-5 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
[0007] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.
[0008] Preferably, the mixing and ball milling treatment is performed at a ball milling speed of 1000-1500 r / min and the ball milling is performed for 2 hours.
[0009] Preferably, the preparation method of the silicon carbide conditioning agent is: S101: irradiating silicon carbide in a proton irradiation box for 5-10 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 2-4 parts of silane coupling agent KH550, 1-3 parts of glass fiber, 2-5 parts of sodium lignin sulfonate solution and 0.25-0.35 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
[0010] Preferably, the mass fraction of the sodium lignin sulfonate solution is 4-6%.
[0011] Preferably, the irradiation power of the proton irradiation box is 400-450W.
[0012] Preferably, the stirring speed of the stirring modification treatment is 450-500 r / min, and the stirring time is 20-30 min.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The energy storage wire and cable adhesive of the invention adopts silicone rubber, carbon black, stearic acid, flame retardant and other raw materials, and by adding calcite additives and silicon carbide regulators to coordinate the two, the flame retardant and dielectric coordinated balance of the obtained product, as well as the weather resistance and ultraviolet stability of the product are remarkable; the calcite additive adopts calcite, sodium silicate solution and lanthanum oxide to fully blend to obtain calcite liquid, and dry flaky talcum powder, nano silica sol and dopamine hydrochloride solution are fully blended to obtain a flaky talcum powder modifier, and the flaky talcum powder modifier is obtained by blending the raw materials and coordinating the flaky talcum powder. The stone powder modifier improves the calcite liquid, and the obtained calcite additive enhances the system performance balance in the system. Meanwhile, the silicon carbide regulator uses silicon carbide irradiated with protons to stimulate the activity of silicon carbide. The silane coupling agent KH550, glass fiber, sodium lignin sulfonate solution and hydroxyapatite are fully blended to obtain a modified liquid. The glass fiber and hydroxyapatite in the modified liquid are coordinated and matched to improve silicon carbide. The synergistic effect of the silicon carbide regulator and the calcite additive is enhanced, and the performance of the product is further improved. DETAILED DESCRIPTION
[0014] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] A method for preparing an energy storage wire and cable adhesive according to the present embodiment comprises the following steps: Step 1: Weigh the raw materials by weight: 10-15 parts of silicone rubber, 4-6 parts of calcite additive, 3-5 parts of silicon carbide regulator, 4-7 parts of flame retardant, 2-5 parts of carbon black, 2-4 parts of stearic acid, 1-3 parts of dimethyl silicone oil, 2-4 parts of dicumyl peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
[0016] The silicone rubber of this embodiment is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 110-115° C., and the mixing time is 20-30 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
[0017] The preparation method of the calcite additive of the present embodiment is: S01: 5-8 parts of calcite, 2-4 parts of sodium silicate solution, and 1-3 parts of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 4-6 parts of dry flaky talc, 1-3 parts of nano-silica sol, and 2-5 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
[0018] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.
[0019] The mixing and ball milling process of this embodiment has a ball milling speed of 1000-1500 r / min and the ball milling is performed for 2 hours.
[0020] The preparation method of the silicon carbide conditioning agent of this embodiment is: S101: irradiating silicon carbide in a proton irradiation box for 5-10 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 2-4 parts of silane coupling agent KH550, 1-3 parts of glass fiber, 2-5 parts of sodium lignin sulfonate solution and 0.25-0.35 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
[0021] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4-6%.
[0022] The irradiation power of the proton irradiation box in this embodiment is 400-450W.
[0023] The stirring speed of the stirring modification treatment in this embodiment is 450-500 r / min, and the stirring time is 20-30 min.
[0024] Example 1. A method for preparing an energy storage wire and cable adhesive according to the present embodiment comprises the following steps: Step 1: Weigh the raw materials by weight: 10 parts of silicone rubber, 4 parts of calcite additive, 3 parts of silicon carbide regulator, 4 parts of flame retardant, 2 parts of carbon black, 2 parts of stearic acid, 1 part of dimethyl silicone oil, 2 parts of diisopropylbenzene peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
[0025] The silicone rubber of this embodiment is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 110° C., and the mixing time is 20 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
[0026] The preparation method of the calcite additive of the present embodiment is: S01: 5 parts of calcite, 2 parts of sodium silicate solution, and 1 part of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 4 parts of dry flaky talc, 1 part of nano silica sol, and 2 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
[0027] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 3%.
[0028] The mixing ball milling process in this embodiment has a ball milling speed of 1000 r / min and a ball milling time of 2 h.
[0029] The preparation method of the silicon carbide conditioning agent of this embodiment is: S101: irradiating silicon carbide in a proton irradiation box for 5 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 2 parts of silane coupling agent KH550, 1 part of glass fiber, 2 parts of sodium lignin sulfonate solution and 0.25 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
[0030] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4%.
[0031] The irradiation power of the proton irradiation box in this embodiment is 400W.
[0032] The stirring speed of the stirring modification treatment in this embodiment is 450 r / min, and the stirring time is 20 min.
[0033] Example 2. A method for preparing an energy storage wire and cable adhesive according to the present embodiment comprises the following steps: Step 1: Weigh the raw materials by weight: 15 parts of silicone rubber, 6 parts of calcite additive, 5 parts of silicon carbide regulator, 7 parts of flame retardant, 5 parts of carbon black, 4 parts of stearic acid, 3 parts of dimethyl silicone oil, 4 parts of dicumyl peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
[0034] The silicone rubber of this embodiment is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 115° C., and the mixing time is 30 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
[0035] The preparation method of the calcite additive of the present embodiment is: S01: 8 parts of calcite, 4 parts of sodium silicate solution, and 3 parts of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 6 parts of dry flaky talc, 3 parts of nano silica sol, and 5 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
[0036] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 6%.
[0037] The mixing and ball milling process in this embodiment was carried out at a ball milling speed of 1500 r / min and the ball milling was carried out for 2 h.
[0038] The preparation method of the silicon carbide conditioning agent of this embodiment is: S101: irradiating silicon carbide in a proton irradiation box for 10 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 4 parts of silane coupling agent KH550, 3 parts of glass fiber, 5 parts of sodium lignin sulfonate solution and 0.35 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
[0039] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 6%.
[0040] The irradiation power of the proton irradiation box in this embodiment is 450W.
[0041] The stirring speed of the stirring modification treatment in this embodiment is 500 r / min, and the stirring time is 30 min.
[0042] Example 3. A method for preparing an energy storage wire and cable adhesive according to the present embodiment comprises the following steps: Step 1: Weigh the raw materials by weight: 12.5 parts of silicone rubber, 5 parts of calcite additive, 4 parts of silicon carbide regulator, 5.5 parts of flame retardant, 3.5 parts of carbon black, 3 parts of stearic acid, 2 parts of dimethyl silicone oil, 3 parts of diisopropylbenzene peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
[0043] The silicone rubber of this embodiment is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 112° C., and the mixing time is 25 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
[0044] The preparation method of the calcite additive of the present embodiment is: S01: 6.5 parts of calcite, 3 parts of sodium silicate solution, and 2 parts of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 5 parts of dry flaky talc, 2 parts of nano silica sol, and 3.5 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
[0045] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 4.5%.
[0046] The mixing ball milling process in this embodiment was carried out at a ball milling speed of 1250 r / min and the ball milling was carried out for 2 h.
[0047] The preparation method of the silicon carbide conditioning agent of this embodiment is: S101: irradiating silicon carbide in a proton irradiation box for 7.5 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 3 parts of silane coupling agent KH550, 2 parts of glass fiber, 3.5 parts of sodium lignin sulfonate solution and 0.30 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
[0048] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%.
[0049] The irradiation power of the proton irradiation box in this embodiment is 420W.
[0050] The stirring speed of the stirring modification treatment in this embodiment is 470 r / min, and the stirring time is 25 min.
[0051] Comparative Example 1. The difference from Example 3 is that no calcite additive is added.
[0052] Comparative Example 2. The difference from Example 3 is that no flaky talc modifier is added in the preparation method of the calcite additive.
[0053] Comparative Example 3. The difference from Example 3 is that the flaky talc modifier is replaced by flaky talc.
[0054] Comparative Example 4. The difference from Example 3 is that no calcite liquid is added in the preparation method of the calcite additive.
[0055] Comparative Example 5. The difference from Example 3 is that no silicon carbide regulator is added.
[0056] Comparative Example 6. The difference from Example 3 is that no modification liquid treatment is used in the preparation of the silicon carbide regulator.
[0057] Comparative Example 7. The difference from Example 3 is that no silane coupling agent KH550 or glass fiber is added to the modified liquid.
[0058] The conventional performance tests of the products of Examples 1-3 and Comparative Examples 1-7 were carried out, and the UV resistance stability was tested by irradiating the products with a UV intensity of 5 mW / cm2 for 24 hours. The tests were as follows:
[0059] It can be seen from Comparative Examples 1-7 and Example 3 that the product of Example 3 has excellent flame retardant and dielectric properties, and the product has significant UV resistance and stability. The present invention does not add one of the calcite additive and the silicon carbide regulator, and the performance of the product deteriorates significantly. The synergistic effect of the two is most obvious. The preparation method of the calcite additive does not add flaky talc modifier, the flaky talc modifier is replaced by flaky talc, the preparation method of the calcite additive does not add calcite liquid, the preparation of the silicon carbide regulator does not use modifying liquid treatment, and the modifying liquid does not add silane coupling agent KH550 and glass fiber. The performance of the product tends to deteriorate. The silicon carbide regulator improved by the modifying liquid obtained by the specific method of the present invention is combined with the calcite additive of the present invention, and the product performance effect is the most significant. The replacement by other methods is not as obvious as the effect of the present invention.
[0060] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing an energy storage wire and cable adhesive, characterized in that: The following steps are involved: Step 1: Weigh the raw materials by weight: 10-15 parts of silicone rubber, 4-6 parts of calcite additive, 3-5 parts of silicon carbide regulator, 4-7 parts of flame retardant, 2-5 parts of carbon black, 2-4 parts of stearic acid, 1-3 parts of dimethyl silicone oil, 2-4 parts of dicumyl peroxide; Step 2: Add the raw materials according to the above ratio into a mixer and mix them until the mixing is completed to obtain a mixed body; Step 3: vulcanize the mixed body to obtain energy storage wire and cable adhesive.
2. The method for preparing an energy storage wire and cable adhesive according to claim 1, characterized in that: The silicone rubber is methyl vinyl silicone rubber; the flame retardant is magnesium hydroxide; the mixing temperature in the mixer is 110-115° C., and the mixing time is 20-30 minutes; the vulcanization temperature of the vulcanization molding is 150° C., and the vulcanization time is 10 minutes.
3. The method for preparing an energy storage wire and cable adhesive according to claim 1, characterized in that: The preparation method of the calcite additive is: S01: 5-8 parts of calcite, 2-4 parts of sodium silicate solution, and 1-3 parts of lanthanum oxide are mixed to obtain a calcite solution; S02: Stir and mix the flaky talc powder in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry; 4-6 parts of dry flaky talc, 1-3 parts of nano-silica sol, and 2-5 parts of dopamine hydrochloride solution are fully blended to obtain a flaky talc modifier; S03: The flaky talc modifier and the calcite liquid are mixed and ball-milled in a weight ratio of 3:
5. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a calcite additive.
4. The method for preparing an energy storage wire and cable adhesive according to claim 3, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.
5. The method for preparing an energy storage wire and cable adhesive according to claim 3, characterized in that: The mixing and ball milling treatment is performed at a ball milling speed of 1000-1500 r / min and the ball milling is performed for 2 hours.
6. The method for preparing an energy storage wire and cable adhesive according to claim 1, characterized in that: The preparation method of the silicon carbide regulator is: S101: irradiating silicon carbide in a proton irradiation box for 5-10 minutes, and obtaining irradiated silicon carbide agent after the irradiation is completed; S102: 2-4 parts of silane coupling agent KH550, 1-3 parts of glass fiber, 2-5 parts of sodium lignin sulfonate solution and 0.25-0.35 parts of hydroxyapatite are mixed to obtain a modified solution; The irradiated silicon carbide agent and the modifying liquid are stirred and modified in a weight ratio of 2:
5. After the stirring is completed, the mixture is filtered and dried to obtain a silicon carbide regulator.
7. The method for preparing an energy storage wire and cable adhesive according to claim 6, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 4-6%.
8. The method for preparing an energy storage wire and cable adhesive according to claim 6, characterized in that: The irradiation power of the proton irradiation box is 400-450W.
9. The method for preparing an energy storage wire and cable adhesive according to claim 6, characterized in that: The stirring speed of the stirring modification treatment is 450-500 r / min, and the stirring time is 20-30 min.